Effects of Acidification and Alkalinization on the Lipid Emulsion-Mediated Reversal of Toxic Dose Levobupivacaine-Induced Vasodilation in the Isolated Rat Aorta - Ok, Seong-Ho (Int J Med Sci, 2016)
The goal of this in vitro study was to examine the effects of pre-acidification and pre-akalinization on the lipid emulsion-mediated reversal of toxic dose levobupivacaine-induced vasodilation in isolated rat aorta. Isolated aortic rings with and without the nitric oxide synthase inhibitor N(ω)-nitro-L-arginine methyl ester (L-NAME) were exposed to four types of Krebs solution (pH 7.0, 7.2, 7.4, and 7.6), followed by the addition of 60 mM potassium chloride. When the toxic dose of levobupivacaine (3 × 10(-4) M) produced a stable and sustained vasodilation in the isolated aortic rings that were precontracted with 60 mM potassium chloride, increasing lipid emulsion concentrations (SMOFlipid(®): 0.24, 0.48, 0.95 and 1.39%) were added to generate concentration-response curves. The effects of mild pre-acidification alone and mild pre-acidification in combination with a lipid emulsion on endothelial nitric oxide synthase (eNOS) phosphorylation in human umbilical vein endothelial cells were investigated by Western blotting. Mild pre-acidification caused by the pH 7.2 Krebs solution enhanced the lipid emulsion-mediated reversal of levobupivacaine-induced vasodilation in isolated endothelium-intact aortic rings, whereas mild pre-acidification caused by the pH 7.2 Krebs solution did not significantly alter the lipid emulsion-mediated reversal of the levobupivacaine-induced vasodilation in isolated endothelium-denuded aortic rings or endothelium-intact aortic rings with L-NAME. A lipid emulsion attenuated the increased eNOS phosphorylation induced by the pH 7.2 Krebs solution. Taken together, these results suggest that mild pre-acidification enhances the lipid emulsion-mediated reversal of toxic dose levobupivacaine-induced vasodilation in the endothelium-intact aorta via the inhibition of nitric oxide.